Research handbook of financial markets - Gurkaynak, Refet S.; Wright, Jonathan H.; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2023)
"The Research Handbook of Financial Markets carefully discusses the histories and current states of the most important financial markets and institutions, as well as explicitly underscoring open questions that need study. By describing the institutional structure of different markets and highlighting recent changes within them, it accurately highlights their evolving nature. Taking the perspective that finance and macroeconomics are intertwined, this illuminating Research Handbook brings together prominent experts to investigate key market interactions. Chapters act as self-contained case studies of particular markets, allowing for a thorough individual examination of each. Ultimately, they offer a holistic understanding of financial markets and the current state of research. Academics and researchers in economics and finance curious about developments within financial regulation and banking will find this comprehensive Research Handbook to be hugely valuable. Market participants will additionally find it to be a useful reference, along with regulators seeking to mitigate financial instability"--
Contents: Introduction to the research handbook of financial markets / Refet S. Gurkaynak and Jonathan H. Wright -- Part I. Central banking -- 1. The federal reserve balance sheet / Kristopher Dawsey, William B. English and Brian Sack -- 2. The balance sheet of the eurosystem / Oreste Tristani -- 3. The bank of Japan's balance sheet / Kosuke Aoki -- 4. Central bank lending / Brian Madigan and William Nelson -- 5. The workings of liquidity lines between central banks / Saleem Bahaj and Ricardo Reis -- Part II. Intermediaries -- 6. Banks / Refet S. Gurkaynak, Jonathan H. Wright and Egon Zakrajsek -- 7. Non-bank financial intermediaries and financial stability / Sirio Aramonte, Andreas Schrimpf and Hyun Song Shin -- 8. Government agencies: Fannie mae and freddie mac / Gillian Burgess, Wayne Passmore and Shane M. Sherlund -- 9. Money market funds / Antoine Bouveret, Antoine Martin and Patrick E. McCabe -- Part III. Money markets -- 10. The federal funds market, pre- and post-2008 / Eric T. Swanson -- 11. The repo market / Benjamin Munyan -- 12. The foreign exchange market / Alain Chaboud, Dagfinn Rime and Vladyslav Sushko -- Part IV. Capital markets -- 13. The treasury and when-issued markets / J. Benson Durham and Roberto Perli -- 14. The municipal bond market / Daniel Bergstresser -- 15. Mortgage-backed securities / Andreas Fuster, David Lucca and James Vickery -- 16. Equity trading / Caroline Fohlin -- 17. Sovereign debt / Leonardo Martinez, Francisco Roch, Francisco Roldan and Jeromin Zettelmeyer -- Part V. Derivative markets -- 18. Interest rate swaps / Bin Wei and Vivian Z. Yue -- 19. Credit default swaps / Antulio N. Bomfim -- 20. Foreign exchange swaps and cross-currency swaps / Angelo Ranaldo -- 21. Inflation hedging products / Stefania D'Amico and Thomas B. King -- 22. Futures and options / Refet S. Gurkaynak and Jonathan H. Wright -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Finance